Street Art is dead. Again and again: Brief State of the (Urban) Art - Filippi, Mauro (Street Art & Urban Creativity, 2020)
What do we mean today, in 2019, by the label ‘Street Art’? Is there really anything that still associate Mexican murals, New York tags and Brazilian pichação with festivals, exhibitions, fairs and millionaire auctions? What links the political and media performances of Banksy to the silent and detailed decorations of Nespoon, the enormous and spectacular installations of Kaws to the tiny and ephemeral characters of Slinkachu, or even the powerful vandalistic actions of Brad Downey to the shining live paintings of Natalia Rak?